Mathematics—Experience of Nightmare to Pleasure using Universal Design for Learning - Gladstone, Ranjith Kingston; Ferrancullo, Jed (11th International Scholars Conference, 2018)
Centuries long, learning Mathematics is a nightmare for students. Many struggle, and most of the time, the students avoid taking Mathematics as much as possible (Gafoor & Kurukkan, 2015). However, there are limited researches on presenting mathematics with fun and creating a conducive learning environment. In this context, how do teachers help students to be motivated to learn Mathematics? How do teachers use the standard Mathematics curriculum in the most fun way? Universal Design for learning (UDL), among other designs, attempts for successful learning. This theoretical study answered the above central research questions. This research used literature as the main source of data to answer. Further, UDL provides educators with practical strategies and techniques to ensure that all their learners meet with higher standards, even to meet with common core state standards (CAST, 2018). The findings reflect in learner’s perspective, UDL provides opportunity for all students to access, participate, and progress in education by reducing the barriers to instruction (Ralabate, 2011). In a multicultural or diverse set-up, researchers are beginning to recognize UDL as a useful tool and resource (Sadowski, 2014). Teacher’s knowledge about attribute and cultural diversity are powerful determinants of learning opportunities and outcomes for different students (Gay, 2002). This study dwelt on the initial questions about the implementation of UDL and in specific—a multi-cultural student-learning set-up, and for Mathematics educators.